DO THEY COMMIT PERJURY?: A STUDY OF REPEATING NARRATIVE OF A CRIME SCENE IN PETER DEXTER’S PARIS TROUT - Wu, Sufen (Sanata Dharma University, 2023)
In Paris Trout, a novel based on actual cases, American writer Pete Dexter arranges a crime scene to be told eight times from different perspectives. A close look at repeating narratives leads to discovering certain discrepancies between the narrator’s account and the characters, especially the criminals’. Dexter renders the criminals’ statements questionable by giving the omniscient heterodiegetic narrator authority and letting his account exert the primary effect. Based on the related laws, this essay finds out that the criminals commit perjury in their statements to exonerate themselves. Moreover, Dexter reveals that their illicit doings are under the defense lawyer’s instructions. By doing so, Dexter puts lawyers’ professional ethics at the center of the story. Showing the truth or winning the lawsuit for the customer? This question is an ethical issue that every lawyer ponders. In order to vigorously promote this kind of thinking, the novelist purposely forms a huge difference in characterization. The defense lawyer is modeled on a lawyer of integrity and honesty who is committed to revealing the truth. Through the ironic change in characterization, Dexter criticizes defense lawyers who don’t have professional ethics, a situation rampant in American society in the 1980s.